Photocatalytic methane oxidation over a TiO2/SiNWs p–n junction catalyst at room temperature - Qui Thanh Hoai Ta; Luan Minh Nguyen; Ngoc Hoi Nguyen; Phan Khanh Thinh Nguyen; Dai Hai Nguyen (Beilstein Journal of Nanotechnology, 2024)
Rapid recombination of charge carriers in semiconductors is a main drawback for photocatalytic oxidative coupling of methane (OCM) reactions. Herein, we propose a novel catalyst by developing a p–n junction titania–silicon nanowires (TiO2/SiNWs) heterostructure. The structure is fabricated by atomic layer deposition of TiO2 on p-type SiNWs. The TiO2/SiNWs heterostructure exhibited an outstanding OCM performance under simulated solar light irradiation compared to the single components. This enhanced efficiency was attributed to the intrinsic electrical field formed between n-type TiO2 and p-type SiNWs, which forces generated charge carriers to move in opposite directions and suppresses charge recombination. Besides, surface morphology and optical properties of the the p–n TiO2/SiNWs catalyst are also beneficial for the photocatalytic activity. It is expected that the results of this study will provide massive guidance in synthesizing an efficient photocatalyst for CH4 conversion under mild conditions.